استراتيجيات التنظيم الذاتي للتعلم وعلاقتها بمستوى التسويف الأكاديمي لدى طلبة السنة الثانية ماستر - مجيدر, بلال; زاغ, سلمى (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة إلى معرفة العلاقة بين استراتيجيات التنظيم الذاتي للتعلم ككل ومستوى التسويف الأكاديمي لدى طلبة السنة الثانية ماستر بكلية العلوم الإنسانية والاجتماعية في جامعة جيجل، ولتحقيق أهداف الدراسة تم إتباع المنهج الوصفي الارتباطي، وتم الاعتماد على مقياس استراتيجيات التنظيم الذاتي للتعلم ومقياس التسويف الأكاديمي لجمع البيانات، ووزعت على عينة بلغت(120) طالبا وطالبة. توصلت الدراسة إلى وجود علاقة ارتباطية دالة إحصائيا بين استراتيجيات التنظيم الذاتي للتعلم ككل ومستوى التسويف الأكاديمي لدى طلبة السنة الثانية ماستر بكلية العلوم الإنسانية والاجتماعية في جامعة جيجل، وعدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) بين متوسطات درجات استجابات طلبة السنة الثانية ماستر بكلية العلوم الإنسانية والاجتماعية بجامعة جيجل في مستوى التسويف الأكاديمي تعزى لمتغيري الجنس والشعبة الأكاديمية. Abstract: This study aims at recognizing the relationship between Self-organizing strategies of learning and level of academic procrastination among second year master students of Human and Social Sciences Faculty at Jijel University. To achieve the research objectives, the correlational descriptive approach has been adopted, depending on both the scales of self-organizing strategies of learning and the academic procrastination for collecting data. They were addressed to )120 ( students. The results reveal the existence of a statistical significant correlational relationship between selforganizing strategies of learning and the level of academic procrastination among second year master students of Human and Social Sciences Faculty at Jijel University. In addition, there are no statistically significant differences at the level of academic procrastination due to the gender variable andthe academic division variable.
بكلية العلوم الإنسانية والاجتماعية في جامعة جيجل
مقال
Keywords: تنظيم ذاتي للتعلم؛ تسويف أكاديمي؛ طلبة سنة ثانية ماستر؛ استراتيجيات تنظيم ذاتي للتعلم; Self-organizing of learning; Academic procrastination; Second year master Students; Self-organizing strategies of learning